Implementasi Program Bantuan Pangan Non Tunai (BPNT) dalam Peningkatan Kesejahteraan Masyarakat di Kecamatan Sipatana Kota Gorontalo - Sri Ayuningsih Doni; Rustam Tohopi; Yacob Noho Nani (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
This student aims to determine how BPNT contributes community in Sipatana District, Gorontalo City. Method used is qualitative findings show that the implementation of BPNT in Sipatana District, particularly in Molosipat U and Tanggikiki sub-districts, has been carried out in accordance with the statutory regulations of 2019 regarding the indicators of power distribution and actor strategies, without any personal intervention in determining beneficiary eligibility. Regarding the characteristics of the implementing institutions, coordination among agencies from the district level to RT/RW has run well and has been conducted transparently and participatively to ensure that the assistance is well-targeted. However, on the indicators of implementer compliance and responsiveness, several obstacles are still found such as delays in disbursement, a lack of direct socialization to the community, and slow responses from the sub-district office in handling complaints from beneficiary families (KPM). These conditions lead to a lack of optimal understanding among beneficiaries regarding the mechanism of aid distribution. Additionally, the impact of BPNT on improving beneficiary welfare remains consumptive in nature and has not fully encouraged economic independence among poor households. Therefore, improvements in service effectiveness, two-way communication, and periodic evaluation are required to enhance BPNT’s contribution in reducing poverty rates and achieving sustainable community welfare.